Is There a Correlation Between Nasolabial Appearance and Dentoalveolar Relationships in Patients With Repaired Unilateral Cleft Lip and Palate?. (January 2020) - Lee, Tara V. N.; Ireland, Anthony J.; Atack, Nikki E.; Deacon, Scott A.; Jones, Timothy E. M.; Matharu, Jason; Wills, Andrew; Al-Ghatam, Rana; Richard, Bruce M.; Ness, Andy R.; Sandy, Jonathan R.
Objective: To determine whether a relationship exists between the aesthetic scores given to photographic records of the nasolabial region of patients with repaired unilateral cleft lip and palate (UCLP) and the 5-Year Olds' Index scores of study models for the same participants. Design: Retrospective study. Setting: University of Bristol Dental Hospital, United Kingdom. Participants: Patients with nonsyndromic UCLP previously enrolled in the Cleft Care UK (CCUK) Study. Methods: The CCUK participants, who had both study models and photographs (frontal and worm's eye view), were identified and their records retrieved. These were rated by 2 consultants and 2 senior registrars in orthodontics. The 5-Year Olds' Index was used to score the study models, and at a separate sitting, a 5-point Likert scale was used to score the cropped frontal and worm's eye view photographs of the same children. The results were analyzed using intraclass correlation coefficients and Cohen κ. Main Outcome Measures: Correlation between the aesthetic scores of the photographic views and the concordant 5-Year Olds' Index scores of the study models. Results: The intraclass correlation coefficient scores showed very poor agreement between the photographic views and their concordant study models. The level of inter- and intra-rater reliability was strongest when scoring the study models. Conclusions: There was no agreement between the scores given to various photographic views and their corresponding study models. Scoring the study models using the 5-Year Olds' Index was the most reliable outcome measure for this age-group.